Can the preemptive use of lornoxicam or paracetamol prevent pain after inguinal hernia repair? A randomized prospective double-blind placebo controlled trial - Alp Alptekin; Zafer Ergul; M Ercan Sonmez; Celil Ugurlu; Haluk Gumus; Hakan Kulacoglu (International Journal of Abdominal Wall and Hernia Surgery, 2022)
INTRODUCTION: Nonsteroidal anti-inflammatory drugs have become a popular part of multimodal analgesic regimens particularly in ambulatory surgery. This study was designed to search the efficacy of preoperative administration of lornoxicam or paracetamol in patients who underwent open inguinal hernia repair. MATERIALS AND METHODS: American Society of Anesthesiologists Classification (ASA) I–III male patients with unilateral primary inguinal hernia scheduled for elective prosthetic repair under general anesthesia were randomly assigned to three groups. Group I patients were infused 100-ml normal saline 30 min before anesthesia (placebo), whereas Group II and Group III patients were given 8 mg lornoxicam or 1,000 mg paracetamol intravenously in 100-ml normal saline. Postoperative pain was treated with patient controlled intravenous morphine. Postoperative pain scores were evaluated with visual analog scale (VAS) in the recovery room and at 1st, 6th, 12th, and 24th hours postoperatively in all groups. Total amount of analgesics. Liker scale and SF-36 form was also used at 4th week follow-up in order assess quality of life. RESULTS: Totally 88 patients were completed the study (G1 = 28, G2 = 30, and G3 = 30). Preemptive use of both lornoxicam and paracetamol resulted in significantly lower recovery room VAS scores in comparison with placebo group (3.93, 3.73, and 5.25). Both lornoxicam and paracetamol groups (G2 and G3) displayed better results at 12th h than placebo group (P = 0.04). VAS scores at 24th hour were similar in three groups. Total morphine consumptions were also similar between the groups at all times. Total postoperative 1-week oral analgesic use was significantly less in G2 (lornoxicam), and G3 (paracetamol) in comparison with G1 (placebo). Quality of life indicators in Likert Scale and SF-36 form were also not different. CONCLUSION: Preemptive use of both lornoxicam and paracetamol may be effective in early postoperative pain control in patients undergo elective open inguinal hernia repair. However, there seems to be no difference between the efficacies of the two agents.